Development of novel microsatellite markers for the Northern Goshawk (Accipiter gentilis) and their utility in cross-species amplification. (1st September 2016) - Haughey, Christy; Sage, George; DeGange, Gabriel; Sonsthagen, Sarah; Talbot, Sandra
The Northern Goshawk (Accipiter gentilis) is a large forest raptor with a Holarctic distribution and, in some portions of its range, a species of conservation concern. To augment previously reported genetic markers, 13 novel polymorphic microsatellite markers were developed to establish individual identification and familial relationships, to assess levels of genetic diversity, and to identify diagnostic markers. Of the 22 loci tested, 13 were polymorphic, seven were monomorphic, and two failed to amplify. This suite of microsatellite loci yielded a combined probability of parental exclusion of 98%; a single individual sampled from a North American population can be reliably identified using a combination of seven of the 13 polymorphic loci. Cross-species screening in Cooper's Hawks (A. cooperii) and Sharp-shinned Hawks (A. striatus) of the 20 loci that successfully amplified in Northern Goshawks identified 13 loci as polymorphic in each species. Six of these loci (Age1303, Age1308, Age1309, Age1312, and Age1314) appeared to be useful in distinguishing between Accipiter species. These markers will be useful to researchers investigating populations of North American accipiters.